Hierarchical based integrated dust management system in a cement manufacturing plant in Malaysia / Vela Lai Kin Ming - Vela, Lai Kin Ming (2017)
Cement is one of the world’s most significantly manufactured materials. Being the major constituents of concrete, cement is manufactured in such huge quantities as statistics shows that, on average, approximately 1 ton of concrete is produced annually for every single person in the world. Although cement industry is widespread with high profitability, it faces many challenges due to environmental concerns and sustainability issues. The industry has a significant contribution to environment imbalances, especially air quality. This is because, in cement manufacturing process, almost every process contributes to generation of significant amount of dust. Therefore, in this study, a cement plant was chosen as a case study. The study was conducted in characterizing dust particles produced, its sources of generation and potential risk. Recommendations were made in mitigating, preventing or minimizing the dust generation using various approaches. Process flow and other data such as the mass balance, dust emissions and the dust management systems were collected from the plant. From the obtained data, characterization of dust was done. The risk assessment done on the dust generation sources revealed that the highest priority of dust management required in quarry, kiln and raw material processing which has high impact rating. This study shows that waste management hierarchy can be used as a model to manage the dust being generated in the plant. By implementing the hierarchical based integrated dust management system, the plant can save significant cost being spent on the product (cement dust) loss, damages to the equipment and frequent change of the dust control technologies. Since the production of cement is involving large area and number of processes, in future the study can be improved by focusing on one process/equipment at one time.